2019
DOI: 10.1111/joop.12298
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the neuroticism – performance link: A dynamic approach to individual differences

Abstract: In the present paper, the relationship between neuroticism and supervisory ratings of performance is examined using a dynamic approach to personality. This approach integrates both within-and between-person differences by looking at individual differences in baseline neuroticism, neuroticism variability and neuroticism attractor strength. Our findings showed that baseline neuroticism related to lower supervisory ratings of performance, and that a high level of baseline neuroticism is particularly detrimental f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…This indicates that variation in the contextual expressions of personality traits are meaningful in the sense that they clarify relations with specific criteria. Taken together, these observations support the inclusion of contextual dynamics as a component of the growing conceptual understanding of personality dynamics (e.g., Sosnowska, Hofmans et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This indicates that variation in the contextual expressions of personality traits are meaningful in the sense that they clarify relations with specific criteria. Taken together, these observations support the inclusion of contextual dynamics as a component of the growing conceptual understanding of personality dynamics (e.g., Sosnowska, Hofmans et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
“…The literature on personality traits has rapidly advanced in recent years to develop the traditional view of traits—as stable, consistent ways of behaving thinking, feeling, which differ between people—to a perspective in which recognizes that within‐person variability is meaningful, nonrandom, and informative for understanding personality (Sosnowska, Hofmans et al, 2020; Woods et al, 2013, 2019). The dynamic approach introduces the idea that temporal or situational fluctuation in trait expression can explain within‐person variation in behavior and consequent outcomes (Sosnowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent empirical studies suggest that assessing stable inter‐individual differences in within‐person contingencies (Mischel & Shoda, 1995; see CAPS in Table 3) between personality states and situational demands (i.e., state levels changing systematically with task demand) may improve predictions of work outcomes beyond traditional personality trait assessments (Minbashian, Wood, & Beckmann, 2010; Wood et al, 2019). Moreover, several studies have investigated relations between personality state fluctuations and job performance (e.g., Debusscher, Hofmans, & De Fruyt, 2014, 2016a, 2016b, 2017; Sosnowska et al, 2019b). Guided by Whole Trait Theory (Fleeson & Jayawickreme, 2015; see WTT in Table 3), Lievens et al (2018) used situational judgement tests to examine people’s hypothetical states in response to different work situations and found that intra‐individual variability incrementally predicted job performance beyond traditional trait measures.…”
Section: Personality Dynamics In Applied Settingsmentioning
confidence: 99%
“…For example, recent empirical studies suggest that assessing stable inter-individual differences in within-person contingencies (Mischel & Shoda, 1995;see CAPS in Table 3) between personality states and situational demands (i.e., state levels changing systematically with task demand) may improve predictions of work outcomes beyond traditional personality trait assessments (Minbashian et al, 2010;Wood et al, 2019). Moreover, several studies have investigated relations between personality state fluctuations and job performance (e.g., Debusscher et al, 2014Debusscher et al, , 2016aDebusscher et al, , 2016bDebusscher et al, , 2017Sosnowska et al, 2019b). Guided by Whole Trait Theory (Fleeson & Jayawickreme, 2015; see WTT in Table 3), Lievens et al (2018) used situational judgment tests to examine people's hypothetical states in response to different work situations and found that intra-individual variability incrementally predicted job performance beyond traditional trait measures.…”
Section: Work and Organizational Psychologymentioning
confidence: 99%